How circular is your tyre: Experiences with extended producer responsibility from a circular economy perspective. (10th October 2020) - Campbell-Johnston, Kieran; Calisto Friant, Martin; Thapa, Kaustubh; Lakerveld, Dirkjan; Vermeulen, Walter J.V.
Abstract: The circular economy (CE) emphasises closing material loops to retain material value. The current practice of tyre recycling in the Netherlands, through a system of extended producer responsibility (EPR), appears an overwhelming success, with claims of 100% recovery. Yet, there is limited critical understanding regarding the system's circularity, considering alternative value retention options and resource recovery outcomes. This study analyses this Dutch tyre EPR system and reflects on how it can be improved from a systemic CE perspective. It uses a qualitative case study approach, using interviews and a review of policy, legal and EPR reporting documents. This paper assesses the governance of this sector and reflects on the existing system, including its circularity and value retention outcomes. Our analysis reveals seven central issues concerning how the EPR system currently functions, resulting in limited circularity and sustainability outcomes, despite high material recovery levels. To address these issues we recommend the continuous improvement of recovery and sustainability targets beyond a single product life cycle, a more transparent and inclusive governance system, as well as a greater focus on sufficiency strategies, e.g. design for durability and a broader transformation of transport models. This paper adds a practical understanding of the capacity of EPR to contribute to CE. Highlights: Evaluating an older circular economy practice to address emerging sustainability concerns. Dutch EPR scheme for tyres achieves high collection and recovery levels. Seven issues are identified, including transparency, monitoring and rationale for recycling options. EPR systems must integrate greater value chain collaboration and continuous improvements.